1981
DOI: 10.1111/j.1365-2052.1981.tb01554.x
|View full text |Cite
|
Sign up to set email alerts
|

‘Malic enzyme’ polymorphism in sheep erythrocytes

Abstract: Summary Malic enzyme or malate dehydrogenase (NADP +). E.C.I.I.I.40. catalyses the reaction: L‐malate + NADP⇄2 pyruvate + CO2+ NADPH Baker & Manwell (1977), in a survey of a number of different enzymes reported that ‘malic enzyme’ was polymorphic in the erythrocytes and certain other tissues of sheep, and indicated that it would be a potentially useful new genetic marker for this species. This paper confirms the existence of the polymorphism in sheep erythrocytes and presents inheritance and breed data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

1992
1992
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 3 publications
1
0
0
1
Order By: Relevance
“…Genetic variation studies have been conducted concerning ME in domestic animals. In the studies performed on sheep (Tucker and Clarke 1980;Yaman and Tucker 1981), S, F, and FS bands were observed, as was the case in the present study of cat breeds. In a study performed on the goats of Argentina (Deza et al 2000), A, AB, and B bands (similar to those bands observed in cats) were observed.…”
Section: Resultssupporting
confidence: 64%
“…Genetic variation studies have been conducted concerning ME in domestic animals. In the studies performed on sheep (Tucker and Clarke 1980;Yaman and Tucker 1981), S, F, and FS bands were observed, as was the case in the present study of cat breeds. In a study performed on the goats of Argentina (Deza et al 2000), A, AB, and B bands (similar to those bands observed in cats) were observed.…”
Section: Resultssupporting
confidence: 64%
“…Οι Baker και υποθέτουν ότι όταν δίνεται έμφαση σε υψηλό ρυθμό ανάπτυξης του οργανισμού, αναμένεται μεγαλύτερη παραλλακτικότητα στις NADP-αφυδρογονάσες, επειδή η ανηγμένη μορφή του NADP χρησιμοποιείται ως πηγή αναγωγικών ισοδύναμων κατά την λιπογένεση. Ιδιαίτερα όσον άφορα το μηλικό ένζυμο, έχει βρεθεί πολυμορφισμός του (Yaman και Tucker, 1981) σε διάφορες φυλές προβάτων. Στον πίνακα 9 παρουσιάζονται οι συχνότητες των δύο αλληλομόρφων του μηλικού ενζύμου σε φυλές προβάτων της Αυστραλίας και της Βουλγαρίας.…”
Section: σχολιασμοςunclassified